Deficits in LTP induction by 5-HT2A receptor antagonist in a mouse model for fragile X syndrome. - Zhao-hui Xu; Qi Yang; Lan Ma; Shui-bing Liu; Guang-sheng Chen; Yu-mei Wu; Xiao-qiang Li; Gang Liu; Ming-gao Zhao (PLoS ONE, 2012)
Fragile X syndrome is a common inherited form of mental retardation caused by the lack of fragile X mental retardation protein (FMRP) because of Fmr1 gene silencing. Serotonin (5-HT) is significantly increased in the null mutants of Drosophila Fmr1, and elevated 5-HT brain levels result in cognitive and behavioral deficits in human patients. The serotonin type 2A receptor (5-HT2AR) is highly expressed in the cerebral cortex; it acts on pyramidal cells and GABAergic interneurons to modulate cortical functions. 5-HT2AR and FMRP both regulate synaptic plasticity. Therefore, the lack of FMRP may affect serotoninergic activity. In this study, we determined the involvement of FMRP in the 5-HT modulation of synaptic potentiation with the use of primary cortical neuron culture and brain slice recording. Pharmacological inhibition of 5-HT2AR by R-96544 or ketanserin facilitated long-term potentiation (LTP) in the anterior cingulate cortex (ACC) of WT mice. The prefrontal LTP induction was dependent on the activation of NMDARs and elevation of postsynaptic Ca(2+) concentrations. By contrast, inhibition of 5-HT2AR could not restore the induction of LTP in the ACC of Fmr1 knock-out mice. Furthermore, 5-HT2AR inhibition induced AMPA receptor GluR1 subtype surface insertion in the cultured ACC neurons of Fmr1 WT mice, however, GluR1 surface insertion by inhibition of 5-HT2AR was impaired in the neurons of Fmr1KO mice. These findings suggested that FMRP was involved in serotonin receptor signaling and contributed in GluR1 surface expression induced by 5-HT2AR inactivation.